Control of American cockroach (Periplaneta americana) and German cockroach (Blattella germanica) by entomopathogenic nematodes - MAKETON, MONCHAN; HOMINCHAN, APINYA; HOTAKA, DARARAT (Revista Colombiana de Entomología, 2010)
Two local and three imported entomopathogenic nematodes (EPNs) were tested for control of the American cockroach (Periplaneta americana) and the German cockroach (Blattella germanica). Only two Steinernematidae caused substantial cockroach mortality; one was a local strain of Steinernema sp. (strain T1), and the other was an imported strain of S. carpocapsae. A homemade bait that contained cat food and attapulgite clay at a ratio of 3:7 (W:W, 10 g total per bait) and 1x106 Steinernema sp. (T1) per bait resulted in 48.0 ± 4.7% mortality of the American cockroach and 57.7 ± 8.0% mortality of the German cockroach. A similar bait containing S. carpocapsae caused 40.0 ± 3.3% mortality of the American cockroach and 86.7 ± 4.7% mortality of the German cockroach. The optimal concentration of Steinernema sp. (T1) and S. carpocapsae to control the American and German cockroach was 1x106 EPNs and 5.4x104 EPNs per bait, respectively. The most susceptible stage of the American cockroach to both EPNs was the last instar, but susceptibility of the German cockroach to both EPNs did not differ among cockroach stages.